Answer:
a)[tex]e^{3}e^{4}=e^{7}[/tex]
b) [tex](e^{3})^{4}=e^{12}[/tex]
c) [tex](e^{3})^{-2}=e^{-6}[/tex]
d) [tex]e^{0}=1[/tex]
Step-by-step explanation:
a) Here we can use the product of powers rule: [tex]x^{a}x^{b}=x^{a+b}[/tex]
[tex]e^{3}e^{4}=e^{7}[/tex]
b) In this ca we use power of a power rule: [tex](x^{a})^{b}=x^{a*b}[/tex].
[tex](e^{3})^{4}=e^{12}[/tex]
c) We use the same rule above.
[tex](e^{3})^{-2}=e^{-6}[/tex]
d) Finally, we can use zero exponent rule: [tex]x^{0}=1[/tex].
[tex]e^{0}=1[/tex]
I hope it helps!